Equivocal evaluation of progressive disease in patients treated with immune checkpoint inhibitors: a challenge for clinical trials and biomarker research. Issue 2 (4th March 2022) - Kyriazoglou, Anastasios; Beuselinck, Benoit
ABSTRACT: We present two patient cases (one with bladder carcinoma and one with renal cell carcinoma) who consulted our department of General Medical Oncology, after having been treated in other hospitals in two clinical trials with immune checkpoint inhibitors and having been dismissed from the trials after 5 months of therapy for progressive disease. They consulted to discuss consecutive treatment opportunities. However, longer follow-up has shown that both patients were dismissed equivocally from both trials. We are worried that equivocal response evaluation in the context of clinical trials with immune checkpoint inhibitors, due to pseudo-progression or delayed responses, can negatively impact trial outcomes as well as biomarker research.